Impairment of cerebral CO2 dynamic vasoreactivity in MCI & AD patients: a multi‐center study of cerebral flow regulation. (20th December 2022) - Marmarelis, Vasilis; Billinger, Sandra A; Chui, Helena C; Joe, Elizabeth B; Shin, Dae; Cardim, Danilo; Hashem, Suhaib; Aaron, Stacey E; Cullum, Munro; Kelly, Brendan; Zhang, Rong
Abstract: Background: Alzheimer's Disease Centers in Los Angeles (USC), Dallas (UT‐SWMC) and Kansas City (KUMC) have joined together to study the regulation of cerebral perfusion through analysis of spontaneous time‐series data using a modeling methodology that previously yielded indications of reduced CO2 dynamic vasomotor reactivity (DVR) in amnestic MCI patients. We report initial results from this ongoing multi‐center study that confirm those preliminary findings and, furthermore, elucidate the effects of slow‐paced breathing. Method: Five‐minute spontaneous changes in arterial blood pressure (ABP), end‐tidal CO2 (etCO2) and cerebral blood flow velocity (CBFV) in middle cerebral arteries were obtained before and after 5‐min session of slow‐paced breathing (8 breaths/minute). Using data from 25 MCI patients, 7 AD patients and 45 age‐matched cognitively normal controls (NC), we obtained predictive models of the dynamic effects of ABP and etCO2 (proxy for blood CO2) upon CBFV via our kernel‐based modeling methodology. These predictive models were used to compute indices (physio‐markers) that quantify the DVR in each participant, as time‐average of the model‐predicted CBFV response to unit‐step change of etCO2 over the first 30 seconds. Result: The obtained DVR indices were significantly different for the 32 patients (MCI and AD lumped together due to small number of AD) vs. 45 age‐matched controls (p= 0.0099). Notably, the delineation between patients and controls improved (p= 0.0011) after a 5‐min session of slow‐paced breathing. Figure 1 shows the average model‐predicted CBFV response to unit‐step change of etCO2 for 32 MCI/AD patients (red line) and 45 controls (blue line) before and after the 5‐min paced‐breathing session. Note the negative average steady‐state CBFV response of the patients (red) that indicates polarity reversal of the normal CO2 vasomotor reactivity (blue). Better delineation between patients and controls is achieved ( p= 2x10 ‐5 ) when the DVR indices from the two sessions, before and after slow‐paced breathing, were averaged (see histograms in Figure 2). Conclusion: Significantly lower DVR indices under resting spontaneous conditions were observed in 32 MCI/AD patients relative to 45 age‐matched controls. This reduction is detected more reliably after 5‐min of slow‐paced breathing. Averaging of the DVR indices obtained before and after slow‐paced breathing improved further this delineation ( p= 2x10 ‐5 ).